Salmonella Acquires Lysosome-associated Membrane Protein 1 (LAMP1) on Phagosomes from Golgi via SipC Protein-mediated Recruitment of Host Syntaxin6 - Madan, Richa (American Society for Biochemistry and Molecular Biology, 2012)
Several intracellular pathogens have developed diverse strategies to avoid targeting to lysosomes. However, they universally recruit lysosome-associated membrane protein 1 (LAMP1); the mechanism of LAMP1 recruitment remains unclear. Here, we report that a Salmonella effector protein, SipC, specifically binds with host Syntaxin6 through its C terminus and thereby recruits Syntaxin6 and other accessory molecules like VAMP2, Rab6, and Rab8 on Salmonella-containing phagosomes (SCP) and acquires LAMP1 by fusing with LAMP1-containing Golgi-derived vesicles. In contrast, sipC knock-out:SCP (sipC(−):SCP) or sipC(M398K):SCP fails to obtain significant amounts of Syntaxin6 and is unable to acquire LAMP1. Moreover, phagosomes containing respective knock-out Salmonella like sipA(−), sipB(−), sipD(−), sopB(−), or sopE(−) recruit LAMP1, demonstrating the specificity of SipC in this process. In addition, depletion of Syntaxin6 by shRNA in macrophages significantly inhibits LAMP1 recruitment on SCP. Additionally, survival of sipC(−):Salmonella in mice is found to be significantly inhibited in comparison with WT:Salmonella. Our results reveal a novel mechanism showing how Salmonella acquires LAMP1 through a SipC-Syntaxin6-mediated interaction probably to stabilize their niche in macrophages and also suggest that similar modalities might be used by other intracellular pathogens to recruit LAMP1.